Prospective Multicenter Study of Chemotherapy-Induced Clostridium (Clostridioides) difficile Infection in Patients With Lung Cancer: North Japan Lung Cancer Study Group Trial 1204 - Toi, Yukihiro; Kobayashi, Takao; Harada, Toshiyuki; Nakagawa, Taku; Mori, Yoshiaki; Kuda, Tomoya; Sugawara, Shunichi (Frontiers in Oncology, 2021)
Background: Diarrhea post-antibiotic use is primarily attributed to mucosal lesions induced by Clostridium (Clostridioides) difficile (C. difficile) infection (CDI). Cancer patients undergoing chemotherapy might have a higher risk of CDI even when prior antibiotics are not used. Thus far, the relationship between lung cancer chemotherapy and the incidence of diarrhea remains unclear. This prospective multicenter study aimed to determine the incidence of CDI in lung cancer patients undergoing chemotherapy. Methods: The presence of C. difficile and its toxins was investigated in lung cancer patients experiencing diarrhea during chemotherapy including paclitaxel (PTX), nanoparticle albumin-bound paclitaxel (nab-PTX), docetaxel (DOC), tegafur-gimeracil-oteracil (S-1), or irinotecan (CPT-11). If grade 2 or higher diarrhea occurred, then a stool culture was performed to detect anaerobic organisms and C. difficile toxins A and B. Additional data were collected through patient interviews and medical chart review. Results: A total of 263 consecutive patients were enrolled in the study; grade 2 or higher diarrhea was observed in 22 patients (8.4%); CDI was confirmed in five of them (1.9%). The incidence of CDI was 22.7% of all diarrhea cases, and 50% of patients treated with PTX were CDI positive; the incidence of CDI was significantly higher in patients treated with PTX (P=0.039). Among the diarrhea cases, CDI patients had significantly worse ECOG performance status (PS) (P=0.043) and a significantly higher neutrophil count (P=0.028) than non-CDI patients. No CDI patients received antibiotics before cancer chemotherapy. Conclusions: Although diarrhea does not always affect a large portion of lung cancer chemotherapy recipients, clinicians should consider the possibility of CDI occurrence in lung cancer patients receiving chemotherapy, particularly PTX, without prior antibiotic exposure.